Pengaruh Penerapan Undang-Undang Perlindungan Anak Terhadap Penurunan Kasus Kekerasan Pada Anak di Indonesia - Wulandari, Yelse Maya (Verdict: Journal of Law Science, 2023)
Legal issues related to child protection in Indonesia are receiving increasing attention, especially as cases of violence against children continue to increase. The Child Protection Law (Law No. 35 of 2014), which is an amendment to Law No. 23 of 2002, was created to protect Indonesian children from violence, exploitation and discrimination. This research aims to see whether the implementation of the Child Protection Law can reduce cases of violence against children in Indonesia. This research uses empirical legal methods with quantitative and qualitative approaches. The results show that the implementation of the Child Protection Law has a major effect in reducing cases of violence against children. However, there are still obstacles in law enforcement and a lack of public awareness. Several problems, such as the lack of coordination between relevant agencies and the lack of socialization of the law to the community, are the main obstacles. Therefore, better socialization efforts and stricter law enforcement are needed to make the protection of children in Indonesia more effective.